Enduring, strategizing, and rising above: workplace dignity threats and responses across job levels - Tilton, Jacqueline (Journal of business ethics, 2024)
Despite a growing body of literature focused on understanding experiences of workplace dignity, attention has centered almost exclusively on employees with lower-level jobs. As a result, little is known about how workplace dignity and indignity are experienced by employees with middle- and upper-level jobs and how their experiences differ from those with lower-level jobs. We address these absences by interviewing employees from a diversity of lower-, middle-, and upper-level jobs about their experiences of indignity at work. We outline common dignity threats, along with typical emotional responses and recourses employees use at each level. We find lower-level employees experience chronic dignity threats from being disrespected, devalued, demeaned, and dehumanized, to which their most typical response is endurance. Middle-level employees experience periodic dignity threats due to undermining of their work, confidence, and reputation. For them, the typical response is strategizing. Finally, on the rare occasions upper-level employees experience dignity threats, it usually is due to a disregard of their special expertise or denial of special rights, to which they respond by rising above.